International postgraduate students adjustment in Malaysia-the role of perceived english language proficiency, acculturation stress, and perceived social support - Lashari, Sana Anwar (2019)
Abstract International students with low proficiency of English language remain at high risk of academic, social, and psychological maladjustment. However, most of the studies on language proficiency have been conducted with non-native English speakers in Anglo Sexon western countries which creates a wide gap in research pertaining to non-native English-speaking countries such as Malaysia. The present research has sought to understand the mechanism by which language proficiency can influence students’ adjustment. The study explores acculturation stress and social support as a construct that potentially connects the body of research investigating language and that examining students’ adjustment. A cross sectional research design was employed. Data was collected from five public universities of Malaysia and a total number of 659 postgraduate international students were recruited using multistage sampling technique. Structural Equational Modeling analysis revealed that the model adequately fit the data collected and it confirmed that English language proficiency is a significant predictor of academic, social and psychological adjustment of international students and this relationship is mediated by acculturation stress and social support. The findings provided significant theoretical implication by extending the nexus of antecedent and outcomes in the international postgraduate students as previously existing models focus on migrants and refugees. Moreover, it also offers recommendations for higher education practitioners and policymakers to invest money for identifying and satisfying the needs of international students for increasing the satisfaction and willingness of international students to recommend Malaysian educational institutions to others.